A new methodology for data reduction in software reliability studies. Issue 3 (1st October 2016) - Loganathan, A.; Muthuraj, R. Jeromia
ABSTRACT: Many business-related activities are now done and administrated using software which are designed and developed specifically for these purposes. Failure-free operation of software is necessary for their effective usage. Several environmental factors have been proposed in the literature for studying reliability of software. Zhang and Pham (2000, Journal of Systems and Software) classified the factors according to their nature into five groups. Information obtained from the personnel involved in the development and use of software may be considered for studying the significance of these factors. Even though data reduction is inevitable in many cases, it can be done optimistically reducing the loss of information. In this article, it is attempted to develop a methodology for reducing the volume of data in software reliability studies with less amount of loss of information.